2018
DOI: 10.3390/ijerph15112461
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stress State Detection Using Genetic Algorithm-Based Feature Selection on EEG Signals

Abstract: In recent years, stress analysis by using electro-encephalography (EEG) signals incorporating machine learning techniques has emerged as an important area of research. EEG signals are one of the most important means of indirectly measuring the state of the brain. The existing stress algorithms lack efficient feature selection techniques to improve the performance of a subsequent classifier. In this paper, genetic algorithm (GA)-based feature selection and k-nearest neighbor (k-NN) classifier are used to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 26 publications
0
77
1
1
Order By: Relevance
“…However, when a participant provides the self-assessment rating for the same video, from the participant rating list (available on [15]), it can be observed that the video from the genre of calmness brings the feeling of stress and vice-versa. Therefore, for this research, the online self-assessment rating is considered to categorize the experiment IDs (either calm or stress) for each participant by Equations (1) and (2), derived from [11,20,21].…”
Section: Dataset Description and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when a participant provides the self-assessment rating for the same video, from the participant rating list (available on [15]), it can be observed that the video from the genre of calmness brings the feeling of stress and vice-versa. Therefore, for this research, the online self-assessment rating is considered to categorize the experiment IDs (either calm or stress) for each participant by Equations (1) and (2), derived from [11,20,21].…”
Section: Dataset Description and Annotationmentioning
confidence: 99%
“…From the time domain, the extracted statistical features are root mean square (F1), square mean root (F2), peak to peak (F3), kurtosis (F4), skewness (F5), kurtosis factor (F6), shape factor (F7), crest factor (F8), and impulse factor (F9). In addition to these statistical feature parameters, Hjorth parameters are also considered to compute the mobility and complexity of the signal [20,23,24]. These two parameters contain the information on the frequency spectrum of the signal.…”
Section: Statistical Features From the Time Domainmentioning
confidence: 99%
“…The system achieved an 86.12% accuracy on average. In [ 80 ], emotional stress state detection using a genetic algorithm and k-NN based on EEG signals is proposed. It achieved a 71.76% accuracy.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Subsequent to presentation of visual stimuli to a subject, multi-channel signals of EEG are recorded, and afterwards, the signal labeling is done based on subject ratings. The previous work on EEG emotional features extraction [25][26][27][28][29] has revealed that there exist several valuable features of time, frequency, and time-frequency that have been evidenced to be efficient in differentiating emotions. Furthermore, there is no standard feature set that has been agreed as the most appropriate for EEG emotion classification.…”
Section: Literature Review On Eeg-based Emotion Recognitionmentioning
confidence: 99%
“…Some of these approaches are demonstrated in Table 2. Few works have presented hybrid methods of evolutionary computer algorithms and classification methods [25], where the objective of these works is to deal with the high dimensionality issue of EEG emotion recognition. Therefore, in this work, we propose a novel fuzzy c-means-genetic algorithm-neural network (FCM-GA-NN) model for EEG emotion recognition.…”
Section: Literature Review On Eeg-based Emotion Recognitionmentioning
confidence: 99%